INCREASING THE EFFICIENCY OF VEGETABLE DRYING USING HIGH-FREQUENCY ELECTROMAGNETIC FIELD - Abduqodirov Ahrorbek; Nodir Eshpulatov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article analyzes the importance of electrotechnological methods, in particular, drying with a microwave electromagnetic field, in increasing the efficiency of vegetable drying technology. The research results showed that microwave drying accelerates drying time by 2 times compared to traditional methods, reduces energy consumption, and better preserves product quality. It was also found that the content of beta-carotene and other nutrients remains at a high level. This article presents scientific foundations and practical recommendations for increasing the efficiency of the microwave drying process.